1993
DOI: 10.1007/bf00569928
|View full text |Cite
|
Sign up to set email alerts
|

Islet microencapsulation: a review

Abstract: The original report on the microencapsulation of islets of Langerhans used sodium alginate and poly-L-lysine (PLL) to form the capsules. Although several alternative materials have subsequently been used with vary-mg degrees of success, it is those studies using islets encapsulated in alginate-PLL-alginate which are reviewed in detail in this article. Since the first report of islet microencapsulation, many studies have demonstrated excellent in vitro viability of encapsulated islets. However, transplantation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 69 publications
0
44
0
1
Order By: Relevance
“…In the case of inadequate biocompatibility, the release of cytokines from nearby activated macrophages, cellular overgrowth and the development of fibrotic tissue surrounding the implant contribute greatly to encapsulated graft failure [7][8][9]. While at least one group has demonstrated that it is possible to produce alginate-polycation microcapsules that induce a minimal immune response [10], first-hand experience and an overview of published works indicate that such promising results are difficult to reproduce, despite the use of similar capsule structures [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of inadequate biocompatibility, the release of cytokines from nearby activated macrophages, cellular overgrowth and the development of fibrotic tissue surrounding the implant contribute greatly to encapsulated graft failure [7][8][9]. While at least one group has demonstrated that it is possible to produce alginate-polycation microcapsules that induce a minimal immune response [10], first-hand experience and an overview of published works indicate that such promising results are difficult to reproduce, despite the use of similar capsule structures [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Several modalities have been developed to shield transplanted islets from the immune system, including macroencapsulation and microencapsulation methods. 8,9 Although microencapsulation has significant advantages over other methods of immunoisolation, and has shown some promise as a viable option for the treatment of diabetes, such as control of the diabetic state in several studies, 9 there are still some limiting factors to the use of the microcapsules, including capsule instability. 8,10,11 One factor contributing to the instability of the alginate microcapsules is a tendency toward capsule swelling as a result of their hygroscopic nature.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although microencapsulation has significant advantages over other methods of immunoisolation, and has shown some promise as a viable option for the treatment of diabetes, such as control of the diabetic state in several studies, 9 there are still some limiting factors to the use of the microcapsules, including capsule instability. 8,10,11 One factor contributing to the instability of the alginate microcapsules is a tendency toward capsule swelling as a result of their hygroscopic nature. This hygroscopic tendency is associated with the presence of divalent cations such as Ca ++ , and the composition, block structure, and molecular size of the alginate molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, graft survival is random and generally too limited for therapeutic application of these microcapsules (8 -10). The reasons for this are presumably the cytotoxicity of the polyamino acid and the mechanical instability of the microcapsules (2,11,12). Microcapsules made of alginate cross-linked with Ba 2ϩ do not share these disadvantages (13).…”
mentioning
confidence: 99%